MATHS

Asked by MelinaLongest side is the hypotenuse so by Pythagoras (6.3)^2 = (5.7)^2 + x^2 Rearranging x = Sqrt((6.3)^2 - (5.7)^2) So x = 2.68 3sf

For this question you need to use Pythagoras' Theorem: the square of the hypotenuse (the longest side, which is opposite the right angle) is equal to the sum of the squares of the other two sides. This is commonly written as: a^2 = b^2 + c^2. In this question the longest side is 6.3, so that is a. And 5.7 is one of the other sides. So you can find the missing side by calculating: a^2 - b^2 = c^2 6.3^2 - 5.7^2 = x^2 squareroot(6.3^2 - 5.7^2) = x = 2.68 (3.s.f.)

Get an answer in 5 minutes

We'll notify as soon as your question has been answered.

Ask a question to our educators

Scoodle's video lessons make learning easy and fun. Try it for yourself, the first lesson is free!